The reality of the Talent Schools in Syria Arab Republic from the view of Students - A Field Study - Zahlok, Maha; Salhab , Sarab (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed at recognize the reality of the Talent Schools in Syria Arab Republic from the view of Students, and at study the different of opinions according to variables (Kind, governorate). To achieve this research goals, questionnaire was designed including (72) items; distributed to the five areas (Students Admission, scholastic environment, Administrators, teachers, Curricula and Methods of Instruction), then applied to a sample of (380) Students for the academic year 2015/2016. The present research used the descriptive analytical approach.Validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Damascus and Tishreen universities. The final results showed that the reality of the Talent Schools in Syria were middle degree. In fact there are no found differences about the reality of the Talent according to variables (Kind, governorate). Research suggestions to doing training courses for Teachers of talent schools before joining scholastic teaching, as well as carrying further researches about the problems of the Gifted Students.